THE ROLE OF NURSES IN CARING FOR PATIENTS WITH DIABETES MELLITUS (REMUNOM, 2025)
The objective was to describe diabetes mellitus, its clinical signs, diagnosis, and possible complications, demonstrate the difference nurses can make in the lives of patients with diabetes mellitus, as well as the promotion of care for a good quality of life, and analyze and describe the care that leads people with diabetes mellitus to a healthier life. This quantitative and qualitative study involved 14 patients treated at a diabetes mellitus treatment unit. Data analysis was performed using Bardin's Content Analysis method. It was observed that diagnosis was based on capillary blood glucose and laboratory tests, and many patients did not receive information about disease prevention. They recognize the role of nurses in assisting with self-care. Awareness of the disease was considered important for treatment, improving quality of life, and avoiding complications. It is concluded that diabetes requires controlling blood glucose levels through healthy habits and consistent medication use. Professionals should prioritize quality of life, ensuring treatment, and preventing complications. The study may contribute to demonstrating that primary health care initiatives require greater support from administrators.